Preliminary Development of an Item Bank and an Adaptive Test in Mathematical Knowledge for University Students - Ghio, Fernanda Belén (2022)
In the last decades, the development of computerized adaptive testing (CAT) has allowed more precise measurements with a smaller number of items. In this study, we develop an item bank (IB) to generate the adaptive algorithm and simulate the functioning of CAT to assess the domains of mathematical knowledge in Argentinian university students (N=773). Data were analyzed from the Rasch model. A simulation design created with the R software was used to determine the necessary items of the IB to estimate examinee ability. Our results indicate that the IB in the domains of mathematical knowledge is adequate to be applied in CAT, especially to estimate average ability levels. The use of CAT is recommended for rapidly generating indicators of the knowledge acquired by students and to design educational strategies that enhance student performance. Results, constrains, and implications of this study are discussed.